The impact of interest rates and inflation towards the shares prices of property sector / Mohd Zailani Zakaria - Zakaria, Mohd Zailani (2001)
This project paper was conducted to answer the question whether Interest Rates and Inflation influence the performance of share prices in Property Sector. The study is focus on the Kuala Lumpur Stock Exchange Property Index that represents all property stock in KLSE. In order to measure the Interest Rates, Kuala Lumpur Interbank Offer Rates (KLIBOR) are used, where else Consumer Price Index (CPI) are used to measure the rate of Inflation. Both are considered as independent variables to test whether these factors are significant or not towards the performance of share price of the property sector as a dependent variable. From the empirical finding, it can be concluded that both the Interest Rates and Inflation have a negative relationship with share price of Property Sector. It means that the inverse relationship exist between independent variables and dependent variable. In conclusion, it's true that the Interest Rates and Inflation give an impact to the Property Market. Lastly, this study also focus on the performance of Property Sector for the five years past since January 1996 until December 2000. All the variables used are calculated In quarter average.